2017
DOI: 10.1111/ggi.13208
|View full text |Cite
|
Sign up to set email alerts
|

Community intervention to increase neighborhood social network among Japanese older adults

Abstract: The present study found that participants of the intervention expanded their neighborhood social network, but non-participants did not. This finding shows that community interventions using university resources could increase older adults' neighborhood social networks. Geriatr Gerontol Int 2018; 18: 462-469.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 21 publications
(39 reference statements)
2
15
0
Order By: Relevance
“…Depressed older adults tend to have more fragile social networks, which was reported to be related to a greater propensity toward suicidal thoughts [42]. A previous community intervention that used a group-based approach to increase the social networks of older adults showed promising results [43], consistent with our study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Depressed older adults tend to have more fragile social networks, which was reported to be related to a greater propensity toward suicidal thoughts [42]. A previous community intervention that used a group-based approach to increase the social networks of older adults showed promising results [43], consistent with our study.…”
Section: Discussionsupporting
confidence: 89%
“…A large community-based observational study showed that infrequent social interactions was significantly associated with depression in older adults [39]. People typically have less contact with friends and colleagues as they age, so it is important to re-establish interpersonal relationships, especially with close friends or neighbors [43]. Our program aimed to strengthen the autonomy of village-dwellers; healthy local committee members were responsible for monitoring the at-risk older adults, and group activities were used to encourage reciprocal care.…”
Section: Discussionmentioning
confidence: 99%
“…Depressed older adults tend to have more fragile social networks, which was reported to be related to a greater propensity toward suicidal thoughts [41]. A previous community intervention that used a group-based approach to increase the social networks of older adults showed promising results [42], consistent with our study.…”
Section: Discussionsupporting
confidence: 89%
“…A large community-based observational study showed that infrequent social interactions was significantly associated with depression in older adults [38]. People typically have less contact with friends and colleagues as they age, so it is important to re-establish interpersonal relationships, especially with close friends or neighbors [42]. Our program aimed to strengthen the autonomy of village-dwellers; healthy local committee members were responsible for monitoring the at-risk older adults, and group activities were used to encourage reciprocal care.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings emphasize the importance of a sustained effort to increase social networks within communities to protect the ikigai of those whose human capital is in the process of decline. For example, it was demonstrated that a university‐led community intervention providing opportunities for social participation and communication among neighborhoods could increase the extent and value of social networks for Japanese elderly (Harada et al., ). Our results also show that more than 40% of the participants increased both weak ties and strong ties over the 4‐year study.…”
Section: Discussionmentioning
confidence: 99%